Antimicrobial susceptibility of gram-negative bacilli isolated from intra-abdominal and urinary-tract infections in Mexico from 2009 to 2015: Results from the Study for Monitoring Antimicrobial Resistance Trends (SMART). - Alfredo Ponce-de-Leon; Eduardo Rodríguez-Noriega; Rayo Morfín-Otero; Dora P Cornejo-Juárez; Juan C Tinoco; Areli Martínez-Gamboa; Carmen J Gaona-Tapia; M Lourdes Guerrero-Almeida; Alexandra Martin-Onraët; José Luis Vallejo Cervantes; José Sifuentes-Osornio (PLoS ONE)
Antimicrobial resistance is an increasing worldwide concern, which poses unique challenges for the effective prevention and treatment of several infections, especially the ones triggered by organisms producing extended-spectrum β-lactamases (ESBL). Here, we present the surveillance results of the Study for Monitoring Antimicrobial Resistance Trends (SMART) of Gram-negative bacilli isolated from intra-abdominal infections (IAI, n = 1,235) and urinary-tract infections (UTI, n = 2,682), collected in Mexico from 2009 to 2015. Susceptibility and ESBL status were determined according to the Clinical and Laboratory Standards Institute (CLSI) broth microdilution method. Both E. coli (57%) and K. pneumoniae (12%) were the most frequently reported organisms, as well as the ones with the highest prevalence of ESBL-producing isolates (54% and 39%, respectively). The overall prevalence of ESBL-producing organisms was higher in nosocomial infections than in community-acquired infections (21% vs. 27%). The ESBL rates were 36% for IAI (953/2,682) and 37% for UTI (461/1,235). In addition, ertapenem, imipenem and amikacin were the antibiotics that mostly preserved bacterial susceptibility. Our results show consistency with global trends, although higher than the rates observed in Latin America.